Message in a bottle : a story of love lost and found - Mandoki, Luis (Warner Brothers, 1999)
Grieving widower Garret Blake builds boats for a living. Rebuilding his life- that's another matter. But that's before Theresa Osborne comes to his North Carolina village. Theresa, a lonely divorcee and researcher for the Chicago Tribune, knows Garret is the author of the message she found inside a bottle on a Cape Cod beach. And she knows the message spoke to her in a way that profoundly touched her heart. Kevin Costner as Garret and Robin Wright Penn as Theresa bring high-voltage starpower to Message in a Bottle, a tale of love lost and found based on Nicholas Sparks' bestseller and directed by Luis Mandoki (White Palace, When a Man Loves a Woman). "You choose - the past or the future. Pick one and stick with it," Garret's spry father Dodge (Paul Newman) advises. The advice sticks. so does the impact of this tender, movingly filmed tale.